Porovnání mzdových systémů České republiky a Německa - Vaněk, David (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Bakalářská práce je zaměřena na porovnání mzdových systému v České republice a v Německu. Teoretická část je zaměřena na popis tvorby hrubé mzdy a stanovení odvodů daní, sociálního a zdravotního pojištění v jednotlivých státech. Praktická část je pojata jako příklad výpočtu mezd určené skupiny zaměstnanců a jejich porovnání. Závěr je zaměřen na zhodnocení obou systémů.

The bachelor's thesis is focused on confrontation of the payroll system in the Czech Republic and Germany. The theoretical part is aimed at describing the formation of gross wages and the determination of taxes, social contributions and health insurance in the both of states. The practical part is conceived as an example of calculation of wages for group of employees and their comparison. The conclusion focuses on the evaluation of both systems.
Cofrontation of the payroll systems in the Czech Republic and Germany
Keywords: mzda; plat; mzdový systém; daně; wage; pay; payrol system; taxes